Lilay - Bravo, Becky; Joson, Rommel; Pastor, Boots S. Agbayani (Quezon City Lampara Publishing House, Inc., 2011)
"One fine morning in the town of Matubig, the people wake up to find their water gone. They have no water to cook their food, no water for the baths, no water to tend to their animals and plants. All of them begin to smell. They are thirsty, so very thirsty, and that is the worst thing of all."
Stories with moral values.
Text in English and Filipino.
Keywords: Water supply -- Fiction